Sistem Pendukung Keputusan Pemilihan Supplier Bahan Baku Pengadaan Material Golf Bag Custom Berbasis Simple Additive Weighting - Julianto, Indri Tri; Dzulkhomzah, Moh Rival (Institut Teknologi Garut, 2025)
Selecting the right raw material supplier is crucial for the sustainability of a company's business operations. This study focuses on the development of a web-based decision support system to optimize the supplier selection process. The Simple Additive Weighting (SAW) method was chosen due to its ease of implementation and its ability to handle multiple criteria. The system takes into account various key factors, including price, delivery speed, type, discount, quality, service, warranty, payment terms, and return policy. Evaluation results show that the developed decision support system is capable of providing more accurate and objective supplier recommendations compared to the previously used manual method. Therefore, this system is expected to improve the efficiency of raw material procurement and support better decision-making.